The Role of Legal Theory in the Era of Digital Globalization: A Perspective of Law Theory as a Tool of Social Engineering - Jeremy Zefanya Yaka Arvante; Aditya Yuli Sulistyawan; Yayan Puji Riyanto (PROGRAM STUDI MAGISTER HUKUM FAKULTAS HUKUM UNIVERSITAS DIPONEGORO, 2025)
The background of this research begins with the fact that modern society follows an exponential pattern of life, where society develops rapidly, leading to a gap between the new lifestyle and the laws that govern it. This is due to the static nature of law and its relatively slow process of reform and adaptation in comparison to the rapid development of society. Based on this problem background, the aim of this study is to analyze the theoretical review of sociological jurisprudence theory in the context of law and society in the era of digital globalization and to analyze and examine the role of legal theory in social life in the digital globalization era, from the perspective of law theory as a tool of social engineering. The research method used in this study is qualitative, with a conceptual, analytical, and philosophical approach. The findings of the research indicate that, given the VUCA (Volatile, Uncertain, Complex, and Ambiguous) characteristics of society, there is a need for the embodiment of law as social engineering in the process of change, and law as social control is also required as a means of controlling social engineering. The conclusion drawn from this study is that the theory of social engineering is ineffective if a country has characteristics with a positivist approach to law. Therefore, a country’s legal system must adopt a pluralistic approach to integrate aspects that go beyond just positive law.